Anatomical changes of Pea(Pisum sativum L.cv Massey Gem) and wheat (Triticumaestivum L.var Machetti) leaves exposed to Uv-B radiation = Perubahan struktur anatomi daun kacang ercis ... - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1995)
ABSTRACT: Pea leaves exposed to UV -B increased their leaf thickness at the mid-rib area, but lowered thickness at non vascular bundle areas. In wheat leaves, both leaf thickness at the mid-rib and non vascular bundle areas increased under UV-B radiation. UV-B radiation appeared to damage the adaxial epidermal and some mesophyll cells of pea leaves, but not in wheat. Electron microscopical studies showed that the general structure of cells from treated pea leaves was different to that control leaves. The collapse of epidermal cells was extreme in some areas, leading to disappearance of the protoplasm with the cell wall becoming pressed, leaving a small structure filled with granular material. Collapsed epidermis was accompanied by some internal damage to palisade layers, where most of cells were disorganized, being empty and columnar. Damaged palisade samples from low and high UV -B treated leaves contained altered chloroplasts and disorganized cells. The altered chloroplasts structure displayed a more open system of thylakoids and lamella membranes. Their photosynthetic lamellae tended to be swollen, with a reduction in thylakoid number, smaller grana, an increase in intergrana spaces, more osmiophilic globuli and poorly defined membranes. Mitochondria were sometimes smaller, with fewer cristae and showed poor membrane structure. In contrast, the general ultrastructure of cells from treated wheat leaves was similar to that of the control leaves.